An early pipeline framework for assessing vendor AI solutions to support return on investment - Charles E. Binkley; David Bouslov; Ali Zaidi; Lauren Kaye; Ralph Whalen; Sameer Sethi; Jose Azar (npj Digital Medicine)
Abstract The success of AI solutions in health systems depends on governance from use case inception through deployment and auditing. This proposed early pipeline governance framework for vendor AI solutions highlights a four-pronged approach: strategic alignment, executive sponsorship, impact and value case assessment, and risk assessment. Each component can be scaled to health systems of any size and the risk and impact assessments can take place simultaneously or sequentially.